2020
DOI: 10.1017/s0016756820001065
|View full text |Cite
|
Sign up to set email alerts
|

The granite porphyry hidden in the Shuangjianzishan deposit, southern Great Xing’an Range, NE China: geochronology, isotope geochemistry and tectonic implications

Abstract: The Shuangjianzishan vein-type Ag-Pb-Zn deposit in the southern Great Xing’an Range (GXR), NE China, is hosted in the slate of the Lower Permian Dashizhai Formation intruded by granite porphyry. In this paper, U–Pb zircon ages and bulk-rock and isotope (Sr, Nd, Pb and Hf) compositions are reported to investigate the derivation, evolution and geodynamic setting of this granite porphyry. It is closely associated with Pb-Zn-Ag mineralization in the southern GXR and contains important geological information relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…
Figure 9. Frequency histogram (a) and selected geologically important sulphur reservoirs (b, Wei and Wang, 1988) of δ 34 S values for pyrite from the Jinying deposit.
…”
Section: Resultsmentioning
confidence: 99%
“…
Figure 9. Frequency histogram (a) and selected geologically important sulphur reservoirs (b, Wei and Wang, 1988) of δ 34 S values for pyrite from the Jinying deposit.
…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that the SGB and all of NE China was under an extensional setting during Late Jurassic -Early Cretaceous times (Wu et al 2011;Ouyang et al 2015;Mao et al 2020;Wei et al 2021;Zhang, G. L. et al 2020;Jing et al 2021). The widespread metamorphic core complexes (Wang et al 2011(Wang et al , 2012 combined with the occurrence of bimodal rock suites, A-type granites (Gou et al 2019;Han et al 2021;Zhang, C. et al 2020), alkaline rhyolites, extensional basins and some Au-Mo-REE mineralization in the SGB (Wu et al 2005;Guo et al 2017;) also indicate a Late Jurassic -Early Cretaceous extensional setting.…”
Section: E1 Late Permian (260-250 Ma)mentioning
confidence: 98%
“…However, the exact closure time of the eastern part of the ocean remains controversial, with suggestions including Early-Middle Jurassic (Zorin, 1999;Tomurtogoo et al 2005), Late Jurassic -Early Cretaceous (Kravchinsky et al 2002) and Early Cretaceous (Ren et al 2016). Regardless of the timing of closure, a substantial number of studies have indicated that the late Mesozoic extensional setting in the SGB is related to post-orogenic gravitational collapse and/or subduction-induced back-arc extension related to the closure of the MOO (Wang, Z. H. et al 2015;Fritzell et al 2016;Guan et al 2018;Ji et al 2018Ji et al , 2020Han et al 2021;Shi et al 2020;Wei et al 2021). On Rb versus (Y þ Nb) and (Yb þ Ta) diagrams, most Late Jurassic W-bearing granitoids in this study and late Mesozoic W-related granitoids from previous studies plot in the post-collision granite field (Fig.…”
Section: E1 Late Permian (260-250 Ma)mentioning
confidence: 99%
See 1 more Smart Citation